RANCANG BANGUN E-RAPORT BERBASIS WEB MENGGUNAKAN MODEL USER CENTERED DESIGN DI SMPN 3 KEPANJEN - Fikri, Agil Ali; Pranata, Kurriawan Budi; Susanto, Gaguk (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2024)
E-Raport, which is short for "Electronic Raport" or "E-Rapor," is the process of recording and reporting performance, development, or achievements digitally or electronically. In the context of education and organizations, E-Raport is generally used as an alternative to manual methods in creating and storing reports. In education, E-Raport refers to the application of a computer-based educational information system to record and report student progress, grades, and academic achievements. The main purpose of using information technology in this system is to simplify the reporting process and provide easier access for students, parents, and educators. Researchers have succeeded in developing an E-raport information system at SMPN 3 Kepanjen using the UCD development model. This process begins with the interview and observation stage to analyze and identify user needs. Furthermore, they design the system based on the results of the analysis, followed by the coding, testing, and application maintenance stages. The evaluation results show that the system aspect gets a percentage of 89.33%, the user aspect 87.16%, and the interaction aspect 90.75%, with an overall average of 89.08%. Thus, the design of web-based e- report using the UCD model at SMPN 3 Kepanjen can be categorized as good and feasible.